LITERATURE REVIEW: THE ROLE OF E-MODULES IN IMPROVING VOCATIONAL STUDENTS’ SCIENTIFIC LITERACY SKILLS - Muhammad Nadir; Riyan Arthur; Daryati Daryati (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
Scientific literacy as a part of the 21st century skill set has a strategic position at the vocational level in preparing graduates who are competent, ready to work, and have skills in communicating and collaboration in work. This study will provide an overview of the role of e-modules which are the most widely developed as teaching materials in improving the student’ scientific literacy skills.. The research method used is a literature review by analyzing 5 most relevant national publication articles using the Google Scholar database. The results of the analysis of 5 articles show that e-modules not only answer the challenges of education in responding to technology, but also proven to play an active role in improving the scientific literacy skills of SMK students including critical and creative thinking skills in order to solve the problem. The e-modules contains aspects of scientific literacy and can be integrated with various learning approach according to the characteristic of vocational student, such as Problem Based Learning (PBL), Socio-Scientific Issues (SSI), Science Technology Engineering Mathematics (STEM) and Problem Based Learning (PBL) by the related occurency in daily life to help student build abilities which support scientific literacy skills.